Philocorydoras longus sp. n. (Monogenea, Dactylogyridae) from the gills of Hoplosternum littorale (Siluriformes, Callichthyidae) in Southeastern Brazil and the reassignment of two species from the genus Urocleidoides to Philocorydoras - Yamada, F. H. [UNESP]; Brandaõ, H. [UNESP]; Yamada, P. De. O. F. [UNESP]; Da Silva, R. J. [UNESP] (De Gruyter, 2015)
Philocorydoras longus sp. n. (Dactylogryridae) is described from the gills of the freshwater fish Hoplosternum littorale (Hancock, 1828) (Callichthyidae) from Jurumirim reservoir, Upper Paranapanema River, Saõ Paulo State, Brazil. This new species belongs to the genus Philocorydoras mainly by possessing a curved cirrus accompanied by an accessory piece attached by a conspicuous filament. Philocorydoras longus sp. n. most resembles P. platensis, but differs by having delicate and smaller hooks, grooves in ventral and dorsal anchors, larger cirrus and accessory piece, and ventral bar with a long postero-medial process. Two species of the genus Urocleidoides (U. corydori Molnar, Hanek et Fernando, 1974 and U. margolisi Molnar, Hanek et Fernando, 1974) originally described from the gills of Corydoras aeneus (Gill, 1858) from Talparo River, Trinidad (near Brazil), were transferred to the genus Philocorydoras mostly by the absence of a sinistral vaginal sclerite (i. e., the primary characters of Urocleidoides) and counterclockwise cirral rings (i.e., curved tube, and tapered anteriorly in Philocorydoras). The new species is the fourth species assigned to the genus and the first recorded for Brazil.
Keywords: Ancyrocephalinae; Freshwater fish; Neotropical region; Paranapanema river